Upaya Meningkatkan Keterampilan Proses Sains Dan Hasil Belajar Biologi Dengan Menggunakan Model Pembelajaran Inkuiry Terbimbing Pada Siswa Kelas XB MAN 2 Sungai Penuh Tahun Pelajaran 2017/2018 - Rodiantifitri Nengsih (Pendidikan Biologi STKIP YPM Bangko, 2018)
IPA formed and developed with a process scientific, must also be developed in school tuition as experiences meaningful that can be used to make the development of self next biology as one of the field of ipa provide a variety of learning experience to understanding the concept of and the process of science.Skill the process of science used that they explore and understand the about. Research aims to understand the increase in skill the process of science and study results students through the application of learning guided inquiry. Methods used is class room research by taking advantage 4 ( four ) a stage in class room research including planning, the implementation of the act of, observation, and reflection.The implementation of the an act done as much as 2 ( two ) cycle, every cycle consisting of 2 ( two meeting learning 1 ( one meeting evaluation. The research results show that has been an increase in skill the process of science out of school in droves of biology as many as 17,57 % the same condition was the results of bejar students show some improvement as many as 28,67 %. Can be concluded that using learning guided inquiry model can improved the skills of the process of science and study results students.